A Systematic Review of the Characteristics and Efficacy of Recovery Training for Mental Health Staff: Implications for Supported Accommodation Services - McPherson, Peter; Lloyd-Evans, Brynmor; Dalton-Locke, Christian; Killaspy, Helen (Frontiers in Psychiatry, 2021)
Evidence suggests a link between recovery-oriented practice and service user outcomes in supported accommodation settings. Current clinical guidelines recommend recovery training for supported accommodation staff, however evidence relating to the effectiveness of this type of training is unclear. This review aimed to describe and compare the characteristics and efficacy of existing recovery training packages for mental health staff. The appropriateness and applicability of the interventions was considered in relation to UK supported accommodation services. Initial search processes returned 830 papers. After duplicate removal, inclusion and exclusion criteria were applied to 489 papers, leaving a final sample of seven papers. Data were reviewed using a narrative synthesis approach. The reviewed papers showed variation in the aims, frequency and duration of the training interventions, although all included content consistent with the five-domains of the CHIME model. All interventions used direct, in-person teaching, and prioritised interactive, experiential learning, however a number were limited by the absence of feedback, the use of one-off, rather than repeated/follow-up sessions, and a reliance on classroom-based, rather than in-vivo, training. There was limited evidence to suggest a consistent effect of training on staff or service user outcomes, and there was no clear association between the delivery and design characteristics of the interventions and reported outcomes. In considering the development of recovery training for supported accommodation staff, little guidance can be taken from the reviewed literature. Any training package must be developed with consideration of the unique contextual and organizational characteristics of these services. The authors recommend viewing training as one component of a broader goal of service transformation.